Características epidemiológicas y condición de egreso de pacientes con covid-19 atendidos en el Hospital Regional de Loreto 2020 - Chanchari Rodriguez, Ayvi (2023)
The objective was to determine the relationship that exists between the epidemiological characteristics of person, time and place and the discharge condition of patients with COVID-19 treated at the Regional Hospital of Loreto 2020. The method was quantitative and the design was non-experimental, descriptive. , correlational, retrospective. The population and sample consisted of 203 medical records of patients with COVID-19. The technique was documentary review and the instruments were the epidemiological characteristics data sheet and the patient's discharge condition identification data sheet. The SPSS statistical package was used for data processing and the chi-square statistical test (x2) for correlational analysis. The results were: 62.6% were between 30 and 59 years old, 61.1% were men, 95.6% had independent occupation, 21.2% had hypertension, 12.8% diabetes, 2.5% obesity, 88.7% presented a severe level of COVID-19 disease, 54.7% came from urban areas, 88.7% were treated in the emergency service, 48.8% had a period of illness from 4 to 7 days, 66% had a hospitalization time in Medicine/ICU of less than 7 days. Regarding the patient's discharge condition, 70% resulted in a recovered condition and 30% died. It is concluded that there is a significant relationship between age (p= 0.000), occupation (p= 0.000), hypertension (p= 0.000), diabetes (p= 0.000), disease severity (p= 0.002), origin (p= 0.030), service where care was taken (p= 0.001), time of illness (p= 0.000), hospitalization time of the patient (p= 0.000) with the condition of discharge and no significant relationship was found with sex (p= 0.585 ) and obesity (p= 0.623).